2024
DOI: 10.1051/0004-6361/202348119
|View full text |Cite
|
Sign up to set email alerts
|

Two fluid dynamics in solar prominences

S. J. González Manrique,
E. Khomenko,
M. Collados
et al.

Abstract: Solar prominences contain a significant number of neutral species. The dynamics of the ionised and neutral fluids composing the prominence plasma can be slightly different if the collisional coupling is not strong enough. The differential dynamics can be discerned by tracing line-of-sight velocities using observational techniques. Large-scale velocities can be quantified by measuring the global local and instantaneous displacement of spectral lines by the Doppler effect. Small-scale velocities leave their impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The dynamics associated with multi-fluid plasma physics has been predicted to play a role over very small scales, often below the observational limits of our instrumentation (<1 min, 10 km, e.g. [4,68]). However, as illustrated previously, it may also have an effect on the stability and lifetime cycle of the whole prominence.…”
Section: Observational Evidence Of Pip In Prominences: Current Insightsmentioning
confidence: 84%
See 3 more Smart Citations
“…The dynamics associated with multi-fluid plasma physics has been predicted to play a role over very small scales, often below the observational limits of our instrumentation (<1 min, 10 km, e.g. [4,68]). However, as illustrated previously, it may also have an effect on the stability and lifetime cycle of the whole prominence.…”
Section: Observational Evidence Of Pip In Prominences: Current Insightsmentioning
confidence: 84%
“…The interpretation of this result depends on the assumed hypotheses. Assuming the non-thermal component to be larger for ions than for neutrals, [4] measured line widths consistent with a unique kinetic temperature. Other authors, instead, found different thermal components for the two species under the assumption of a zero non-thermal motion (e.g.…”
Section: Observational Evidence Of Pip In Prominences: Current Insightsmentioning
confidence: 85%
See 2 more Smart Citations
“…However, the spatial resolution, limited either by instrument capabilities or atmospheric seeing conditions, hinders the detection of the finest structures. Numerous authors have endeavoured to identify potential dynamical decoupling between plasma components by measuring sets of ionized and neutral spectral lines targeting optically thin prominence plasma [11][12][13][14][15][16]. Despite inherent uncertainties in these observations, straining the sensitivity limits of the instrumentation used, all studies, except [12], have reported a slight excess in the amplitude of ion variations over neutrals.…”
Section: Introductionmentioning
confidence: 99%